The Effect of Capital Structure, Operational Efficiency, and Sales Growth on the Financial Performance of Food and Beverage Manufacturing Companies Listed on the Indonesia Stock Exchange During the 2020–2024 Period - Nadhifatul Sherlya Putri; Wasti Reviandani (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the effect of capital structure, operational efficiency, and sales growth on the financial performance of manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. This research employs a quantitative approach using secondary data obtained from the annual financial statements of the sampled companies. The research population consists of all manufacturing companies in the food and beverage subsector listed on the IDX, with the sample selected through purposive sampling, resulting in 31 companies. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 25. The results indicate that capital structure does not have a significant effect on the financial performance of the companies. Operational efficiency also does not show a significant effect on financial performance, although it exhibits a positive relationship. In addition, sales growth does not have a significant effect on the financial performance of food and beverage manufacturing companies during the observation period. These findings suggest that improvements in financial performance are not solely determined by funding structure, operational cost efficiency, or sales growth, but are also influenced by other factors such as cost management, business strategy, and prevailing economic conditions.